A System of National Accounts 1968 - United Nations Department of Economic; Social Affairs (United Nations, 1968)
The 1968 System of National Accounts extended the scope of the national accounts substantially by; adding input-output accounts and balance sheets; giving more attention to estimates at constant prices; and making a comprehensive effort to bring the SNA and the Material Product System (MPS) closer together.